Migration and Islamic Ethics Issues of Residence, Naturalization and Citizenship - Jureidini, Ray; Bin, Hamad; Fares Hassan, Said (Studies in Islamic Ethics, 2019)
Migration and Islamic Ethics, Issues of Residence, Naturalization and Citizenship contains various cases of migration movements in the Muslim world from ethical and legal perspectives to argue that Muslim migration experiences can offer a new paradigm of how the religious and the moral can play a significant role in addressing forced migration and displacement Readership: All interested in migration movements including residence, naturalization, and citizenship; Islamic Ethics and Islamic legal debates on movements in and out of the Muslim world, including asylum seekers and refugees.